Pengembangan Sistem Manajemen Servis Suku Cadang Bus (Studi Kasus: PT. Pahala Kencana) - Farid Widyatama; Achmad Arwan; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
One type of land transportation vehicle that is widely used by people is the bus. One of the transportation service providers using buses is PT. Pahala Kencana. The company has several branches of which are located in the city of Malang. Every bus will certainly be treated and maintained in order to maintain quality and safety. The process of bus maintenance and maintenance includes checking submissions and bus parts management. There are several problems including bus crews who want to file a bus check must wait until the bus arrives. The next problem is that when a mechanic submits a bus spare part, the officer cannot see the progress of the bus parts submission while the last problem is that the logistical officer has difficulty recapitulating data and making reports because all processes are carried out manually and has the potential to result in recording errors. To overcome this, a system was created to assist production division officers. This system was developed on a web basis. The process of developing this system uses SDLC waterfall. In the research conducted, 41 functional needs were obtained, 1 non-functional requirements were also obtained, and five types of actors were produced. System implemented using Laravel Framework. The unit test results get 100% results, then integration testing it gets 100% results, then the validation testing it gets 100% results and finally the compatibility test shows that there are no problems when run on different browsers.